Pendeteksian PHP Vulnerabilities Menggunakan Metode Forward Taint Data Analisis - Shyffa Ilmallia Noer Fhadillah; Parman Sukarno; Aulia Arif Wardana (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2020)
This research builds the detection of php scripts using the Forward Taint data analysis method. Research has been carried out to test this attack. However, the accuracy that has been inferred is still very low. This is getting higher because of the false positive generated. So in solving this problem, the forward taint data analysis method performs double checks that will reduce the positive false value generated. Accuracy resulting from this research reached 90%. These results outperform other existing methods.